Long Non-Coding RNA PANTR1 is Associated with Poor Prognosis and Influences Angiogenesis and Apoptosis in Clear-Cell Renal Cell Cancer - Seles, Maximilian; Hutterer, Georg C; Foßelteder, Johannes; Svoboda, Marek; Resel, Margit; Barth, Dominik A; Pichler, Renate; Bauernhofer, Thomas; Zigeuner, Richard E; Pummer, Karl; Slaby, Ondrej; Klec, Christiane; et al. (Cancers, 2020)
POU3F3 adjacent non-coding transcript 1 (PANTR1) is an oncogenic long non-coding RNA with significant influence on numerous cellular features in different types of cancer. No characterization of its role in renal cell carcinoma (RCC) is yet available. In this study, PANTR1 expression was confined to human brain and kidney tissue and was found significantly up-regulated in clear-cell renal cell carcinoma tissue (ccRCC) compared to non-cancerous kidney tissue in two independent cohorts (p < 0.001 for both cohorts). In uni- and multivariate Cox regression analysis, ccRCC patients with higher levels of PANTR1 showed significantly poorer disease-free survival in our own respective cohort (n = 175, hazard ratio: 4.3, 95% confidence interval: 1.45-12.75, p = 0.008) in accordance with significantly poorer overall survival in a large The Cancer Genome Atlas database (TCGA) cohort (n = 530, hazard ratio: 2.19, 95% confidence interval: 1.59-3.03, p ≤ 0.001). To study the underlying cellular mechanisms mediated by varying levels of PANTR1 in kidney cancer cells, we applied siRNA-mediated knock-down experiments in three independent ccRCC cell lines (RCC-FG, RCC-MF, 769-P). A decrease in PANTR1 levels led to significantly reduced cellular growth through activation of apoptosis in all tested cell lines. Moreover, as angiogenesis is a critical driver in ccRCC pathogenesis, we identified that PANTR1 expression is critical for in vitro tube formation and endothelial cell migration (p < 0.05). On the molecular level, knock-down of PANTR1 led to a decrease in Vascular Endothelial growth factor A (VEGF-A) and cell adhesion molecule laminin subunit gamma-2 (LAMC2) expression, corroborated by a positive correlation in RCC tissue (for VEGF-A R = 0.19, p < 0.0001, for LAMC2 R = 0.13, p = 0.0028). In conclusion, this study provides first evidence that PANTR1 has a relevant role in human RCC by influencing apoptosis and angiogenesis.
Keywords: renal cell cancer; clear-cell renal cell carcinoma; oncogene; Linc-POU3F3; Linc01158; long intergenic non-coding RNA; PANTR1; siRNA